1988
DOI: 10.1021/bi00419a010
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide N-alkylphosphoramidates: synthesis and binding to polynucleotides

Abstract: A few different methods for the preparation of oligonucleotide N-alkylphosphoramidates were compared directly. One of these, involving the use of protected nucleoside phosphites as building blocks, provided the requisite N-alkylphosphoramidates via oxidation of the intermediate dinucleoside methyl phosphites with iodine in the presence of the appropriate alkylamine. This method was found to have several attractive features, including the use of building blocks identical with those employed for the synthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 49 publications
3
26
0
Order By: Relevance
“…It is noteworthy that the 9-mer linked only to the dodecanol tail at the 3'-end was also more efficient than the unmodified or acridine-substituted oligomers. Letsinger et al (1986) and Jager et al (1988) have shown that lipophylic substituents may stabilize DNA helical structures. In addition more efficient induction of RNase H cleavage by this oligonucleotide may also result from facilitation of RNase H binding to the hybrid duplex.…”
Section: +1mentioning
confidence: 99%
“…It is noteworthy that the 9-mer linked only to the dodecanol tail at the 3'-end was also more efficient than the unmodified or acridine-substituted oligomers. Letsinger et al (1986) and Jager et al (1988) have shown that lipophylic substituents may stabilize DNA helical structures. In addition more efficient induction of RNase H cleavage by this oligonucleotide may also result from facilitation of RNase H binding to the hybrid duplex.…”
Section: +1mentioning
confidence: 99%
“…Actually, the potential use of oligonucleotides in uiuo is severely hindered by their degradation by nucleases that hydrolyse the phosphodiester backbone. Therefore, modifications of the backbone have been made in order to improve resistance to nucleases, notably, methylphosphonates (Murakami et al, 1985), phosphotriesters (Pless and Ts'o, 1977) phosphorothioates (Stein ef al., 1988) and phosphoramidates (Jager et al, 1988). Another possible modification consists of substituting the natural 1-anomers by [a]-anomers which change the stereochemistry at the C1' position, placing the base at the location normally occupied by the H1' proton.…”
Section: -mentioning
confidence: 99%
“…There are several ways in which oligonucleotides can be made resistant to nucleases. The phosphodiester backbone can be modified: methylphosphonates (11), phosphotriesters (12), phosphorothioates (13), and phosphoramidates (14) have been described. Alternatively, the anomeric configuration of the nucleoside units can be changed.…”
mentioning
confidence: 99%